Addressing racist parents in a paediatric setting: the nuance of zero tolerance policies. (13th December 2021) - Qureshi, Zeshan; Suleman, Mehrunisha; Richards, Alexandra; Sheather, Julian; Bishop, Hugh
Abstract : Healthcare professionals need clearer guidance on responding to racism in paediatric settings, argue Zeshan Qureshi and colleagues